Compstat and Organizational Change in the United States, 1999-2001 - Weisburd, David ([Verlag nicht ermittelbar], 2009)
The purpose of the study was to determine how Compstat programs were being implemented across the United States by examining the diffusion of Compstat and factors associated with its implementation. Another goal of the study was to assess the impact of Compstat on line or patrol officers at the bottom of the police organization. The researchers administered a national survey on Compstat and problem solving in police agencies (Part 1) by mail to all 515 American police agencies with over 100 sworn police officers, and to a random sample of 100 agencies with between 50 and 100 sworn officers. The researchers received a total of 530 completed surveys (Part 1) between June 1999 and April 2000. The researchers distributed an anonymous, voluntary, and self-administered survey (Part 2) between December 2000 and May 2001 to a total of 450 patrol officers at three police departments -- Lowell, Massachusetts (LPD), Minneapolis, Minnesota (MPD), and Newark, New Jersey (NPD). The Compstat Survey (Part 1) contains a total of 321 variables pertaining to executive views and departmental policy, organizational features and technology, and comments about problem solving in police agencies. The Line Officer Survey (Part 2) contains a total of 85 variables pertaining to the patrol officers' involvement in Compstat-generated activities, their motivation to participate in them, and their views on these activities.